Répartition des tâches familiales et satisfaction conjugale de couples à double revenu selon les cycles - Huppé, Micheline; Cyr, Mireille (Canadian Journal of Counselling and Psychotherapy, 2007)
The purpose of this study is to explore the relationship between marital satisfaction and the division of household labour in dual-income couples. Couples completed a questionnaire (Cyr & Huppé, 1990), each person separately, in order to evaluate simultaneously a number of variables related to the division of household tasks: participation in child care and household labour, degree of responsibility, perception of equity and satisfaction. The sample consisted of 115 dual-income couples distributed into six family life cycles. Marital satisfaction was measured using the Dyadic Adjustment Scale (Spanier, 1976). Results indicated that women with children who work in the labour force do twice as many family chores as do their husbands. Marital satisfaction was correlated for women with their perception of equity and for men with their satisfaction with the division of household work. Many differences were also identified with regard to the other variables measured, between men and women. Couples with or without children also presented differences. Discussion emphasizes direction for future studies and implications for the treatment of couples.